LncRNA SNHG6 Silencing Could Arrest Progression of High Grade Colorectal Cancers - Amin Jafari Oliayi; Shahriar dabiri; Malek Hossein Asadi (Iranian Society of Pathology, 2022)
Background & Objective: Colorectal cancer (CRC), like other cancers, needs faster and more accurate identifications. A well-timed prognosis of CRC could be an important turning point in the survival of patients. Supplementary signs, such as long non-coding RNAs (lncRNAs), could be helpful for this purpose. A new possible biomarker for CRC identification is introduced by this study.Methods:  RNA extraction was performed by the RNX-Plus solution for 64 tumor and non-tumor tissues. Complementary DNAs (cDNAs) were synthesized, and quantitative real-time PCR was performed for relative expression level measurement and the data was analyzed statistically using the Prism 6 software. For Small nucleolar host gene 6 knockdown, siRNA was designed based on Reynolds rules. The cells were cultured in their appropriate media, and the siRNA-lipofectamine complex was formed. The transfection complex was presented for sw48, sw480, and sw1116 as CRC cells with different grades. After transfection, the SNHG6/β actin ratio was determined. Then, the distribution of siRNA-treated cells was determined by the Partec flow cytometer instrument and analyzed by the FloMax software.Results: SNHG6 was more expressed in CRC tumors than non-tumor tissues. In tumor tissues, SNHG6 upregulation and tumors' grade progression were concurrent. SNHG6 was upregulated in cases with lymphovascular invasion than in cases with perineural invasion. The knockdown of SNHG6 conduced to G1 arrest in CRC cells, more noticeably in high-grade ones.Conclusion: SNHG6 could be applied as a consideration to differentiate tumor and non-tumor tissues and grade definition in colorectal malignancies, and it could participate in colorectal tumor formation as a cell cycle progressive factor.